Organization of food products on supermarket shelves in Muritiba – Bahia (Research, Society and Development, 2021)
The retail of Brazil undergoes changes every day with the intention of meeting the demands of consumers. Supermarkets reinvent themselves every day so that the visual needs of the organization of the shelves are efficient for customers and thereby increase their profitability. The study was carried out in a supermarket in the city of Muritiba - Bahia, between September and November 2019. The evaluation was carried out in a qualitative way, through the observation of the daily life of a supermarket. For the discussion of the observations, a search for data was carried out to carry out a comparative discussion regarding the organization and existing routines in the sector. Thus, enabling a better understanding of the nature of the variables in order to develop arguments and propose solutions to the problem. The observation was to verify that supermarkets need improvements so that customers can be served in an appropriate and efficient manner. Assign a single employee responsible for the purchasing sector, in addition to employees who check the batches, the validity and if the products have any damage, are essential to ensure the quality of the products offered, as well as to ensure less rework in the organization of the supermarket shelves.